Local commons go global - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Local global interactions is the main thread of an international conference on 'The commons in an age of globalisation'. It will be held from 17 to 21 June 2002, in Victoria Falls, Zimbabwe and is organised by the International Association for...